Teams-Games-Tournament (TGT) to Teach Vocabulary of English for Specific Purpose in Increasing Students’ Self-Esteem - Sunarti Sunarti; Rani Herning Puspita; Abdul Halim (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
The objective of this study was to investigate the implementation of playing game on students’ mastery on vocabulary of ESP viewed from self-esteem in producing words. The investigation were: (1) to know whether Teams-Games-Tournament (TGT) was more effective than Grammar Translation Method (GTM) to teach vocabulary of ESP; (2) to know whether the students whose self-esteem was high had better vocabulary of ESP mastery than those who had low self-esteem; and (3) to prove whether there was an interaction between teaching methods and self-esteem to teach vocabulary of ESP. The research design used for the research was a simple factorial design 2 x 2. Simple Random sampling was used to select 48 students of two classes. Meanwhile, in determining the sample into the experimental and control class, the researcher chose the class randomly. The data were analyzed by using multifactor analysis of ANOVA 2x2 and Tuckey test. The findings of this research revealed: (1) TGT was more effective than GTM in teaching vocabulary of ESP. (2) The students who were taught by TGT had higher vocabulary mastery than those who were taught by GTM. (3) The students having high self-esteem had better ESP vocabulary than those of students with low self-esteem. It is concluded that: 1) Teams-Games-Tournament is more effective than GTM in teaching vocabulary of ESP; 2) The students having high self-esteem have better vocabulary of ESP mastery than those having low self-esteem; 3) There was interaction between teaching methods and students’ self-esteem